1996
DOI: 10.1073/pnas.93.8.3570
|View full text |Cite
|
Sign up to set email alerts
|

Functional protection of dystrophic mouse (mdx) muscles after adenovirus-mediated transfer of a dystrophin minigene.

Abstract: Fast skeletal muscles of mdx (X chromosome-linked muscular dystrophy) mice were injected after birth with a recombinant adenovirus containing a minidystrophin gene, a 6.3-kbp cDNA coding for the N-and Cterminal ends ofdystrophin. Adult muscles were challenged by forced lengthening during tetanic contractions. Stretchinduced mechanical and histological damages were much reduced in injected muscles, in (n = 7) or with the Ad-RSVI3gal (n = 7). When mice were 4 months old muscles were isolated under general anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 29 publications
2
88
0
Order By: Relevance
“…Other groups have shown that the conversion of an important proportion of muscle fibers from dystrophin-negative to -positive was a prerequisite for a physiological functional benefit in the mdx model (30 to 40%). 27 The transduction efficacy presented in this study is close to these values, at least regarding the expression of ␤-gal, and would therefore be compatible with the development of a functional benefit.…”
Section: Figure 7 Lack Of Persistence Of Transduced Fibers In An Acutsupporting
confidence: 78%
See 2 more Smart Citations
“…Other groups have shown that the conversion of an important proportion of muscle fibers from dystrophin-negative to -positive was a prerequisite for a physiological functional benefit in the mdx model (30 to 40%). 27 The transduction efficacy presented in this study is close to these values, at least regarding the expression of ␤-gal, and would therefore be compatible with the development of a functional benefit.…”
Section: Figure 7 Lack Of Persistence Of Transduced Fibers In An Acutsupporting
confidence: 78%
“…However, the original nature of dystrophic muscles makes difficult the evaluation of potential additional damage raised by the electrotransfer procedure in dystrophic animals. For example, the mdx skeletal muscle is known to be especially sensitive to eccentric contractions, 27,52,53 and one may not exclude that the electrotransfer protocol may be more detrimental in certain muscular pathologies than in others.…”
Section: Figure 7 Lack Of Persistence Of Transduced Fibers In An Acutmentioning
confidence: 99%
See 1 more Smart Citation
“…12 To date, AdV-mediated dystrophin gene transfer has generally been performed in immunologically immature (neonatal) mdx animals during the period that precedes the onset of major myofiber necrosis and reduced forcegenerating capacity. [25][26][27] Under these conditions, the immune response against AdV-infected cells is significantly less pronounced than in adult animals, and the longevity of dystrophin gene expression can thus be sufficient to reduce histological evidence of disease progression several weeks later 26 despite the absence of immunosuppressive therapy. However, in human patients suffering from DMD, the diagnosis is usually made at a much later stage due to the development of symptomatic muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
“…1 Skeletal muscle is an excellent target for rAd-mediated gene therapy, [2][3][4] and rAd has delivered therapeutic genes efficiently to neonatal muscle. 5 However, the rAd-mediated gene transfer to skeletal muscle has been criticized for two problems: the limited expression of the transgene and the poor tropism of adenovirus for mature skeletal muscle fibers.…”
Section: Introductionmentioning
confidence: 99%